PELAKSANAAN LELANG EKSEKUSI OLEH KREDITUR TERHADAP JAMINAN SEBAGAI SARANA PELUNASAN HUTANG DEBITUR BERDASARKAN PASAL 6 AYAT (1) UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN - Akira Widyanti (Rechtsregel : Jurnal Ilmu Hukum, 2020)
In this case, the Jakarta III KPKNL received an application for the Mortgage Rights Execution Auction submitted by PT. Bank Nasional Indonesia (Persero) Tbk, Regional Remedial & Recovery Jakarta Senayan. This request is based on the inability of PT. UNITECH INDONESIA as a debtor to pay off debt to PT. BNI (Persero) Tbk. PT. UNITECH INDONESIA is granted a period of time as stated in the Credit Agreement Number 14.066 signed by both parties for 12 (twelve) months from May 28, 2014 to May 27, 2015. However, up to the specified time the debtor has not yet completed their obligations . So that creditors provide credit restructuring opportunities in October 2015 to settle their obligations. At the appointed time, PT. UNITECH INDONESIA still cannot complete its obligations. Bearing this in mind, PT. BNI (Persero) Tbk made an effort by issuing Somasi I Letter on August 15, 2016, Somasi Letter II on September 13, 2016 and Somasi Letter III on February 27, 2017, but this did not produce results. The settlement of this case is by submitting a request to re-auction the execution of mortgage rights which had previously been submitted but were unsuccessful. The auction application was submitted on May 17, 2018 to the Jakarta III KPKNL. By submitting data to meet the requirements contained in the Regulation of the Director General of State Assets Number 2 / KN / 2017 Concerning Technical Guidelines for Tender Implementation and other relevant regulations, the request is accepted and is expected to be successful in paying off debtors' debts to creditors. In this case, the KPKNL has the duty and function of managing state assets. The types of auction services that are often carried out by the Jakarta III KPKNL include Mortgage Rights Execution Auctions, Fiduciary Execution Auctions, Auction Execution of Confiscated Goods, collateral receivables from the State / district court and so on. In this case the writer collected the data through library research and field research. The study was conducted at the Jakarta Office of State Assets and Auction Services (KPKNL) III. And collection of library data such as the 1945 Constitution, the Civil Code, Law Number 4 of 1996 concerning Mortgage Rights, Regulation of the Director General of State Assets Number 2 / KN / 2017 Regarding Technical Guidelines for the Implementation of Auction, Regulation of the Director General of Wealth Number 9 / KN / 2017 concerning the division of tasks in the vertical agency of the Directorate General of State Assets and other relevant regulations.